System Of Tasks Aimed At Forming Skills Of Establishing Cause-And-Effect Relationships In Solving Problems In The Field Of Chemistry Education (Journal of Pedagogical Inventions and Practices, 2026)
This article examines the issues of identifying cause-and-effect relationships among students in the process of teaching chemistry, developing logical thinking, and gradually forming a system of chemical concepts. The author analyzes the role of integrative and interdisciplinary approaches in chemistry education, as well as the possibilities of shaping students’ scientific worldview through the topic “Theory of Solutions.” The significance of using inductive and deductive approaches in studying solutions, establishing cause-and-effect relationships between concepts, and revealing the essence of chemical processes is demonstrated.